Evaluasi Kinerja Operasional Dan Pelayanan Angkutan Sekolah di Kabupaten Sleman Dengan Metode Ipa–Swot - Setyono, Yahya Ramadan; Turasno, Buang (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
School transportation in Sleman Regency faces various problems, including limited number of fleets, operational schedules that are not yet optimal, and the lack of adequate safety facilities. This condition means that some students are not served well and pose a risk to their safety and comfort during their trip. This research aims to evaluate the operational performance and services of school transportation, as well as formulate improvement strategies. The method used is a quantitative and qualitative approach through field surveys, interviews and distributing questionnaires. Service performance is analyzed using the Importance Performance Analysis (IPA) method, while development strategies are prepared through SWOT analysis. The research results show that at departure time, the load factor reaches up to 126.3% in corridor 1 and 118% in corridor 2, which indicates overloading with fleet availability of only 66.67%. Meanwhile, IPA analysis identified priority improvement indicators such as Emergency Response Information, Safety Equipment: glass breakers and APAR, and Safety Belts. The improvement strategy resulting in a SWOT matrix that is used in the short term includes preparing different return schedules and improving safety facilities such as providing fire extinguishers and glass breaking hammers. Long-term improvement strategies include adding corridors to school transportation services and digitizing reporting. It is hoped that this evaluation will become the basis for improving safer, more efficient and equitable school transportation services in Sleman Regency.